2017
DOI: 10.1002/vms3.73
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology and assessment of risk factors for the spread of avian influenza in birds in two Nigerian states

Abstract: Despite modified stamping out eradication policy adopted in Nigeria, there was resurgence in 2015 of highly pathogenic avian influenza (HPAI) H5N1 with greater infectivity. A survey of the risk of spread of HPAI in two HPAI‐infected and ‐uninfected Nigerian states were studied. A cross‐sectional study to detect avian influenza (AI) H5 antibodies was conducted using haemagglutination inhibition (HI) test and enzyme‐linked immunosorbent assay (ELISA). A total of 950 birds’ sera were tested for AI H5 antibodies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 27 publications
1
7
0
1
Order By: Relevance
“…Poor biosecurity practice is a significant risk factor for the higher prevalence of AIV [ 42 ]. Waziri et al [ 43 ] demonstrated that chickens reared in poor biosecurity practices were three times more vulnerable to be spreaders of AIV compared to good biosecurity practicing farms, which is in accordance with the current findings. Osmani et al [ 16 ] conducted a case control study and reported an increased number of farm staffs (OR: 5.2), weekly visit of veterinarians (OR: 3.0), and roaming of village chickens around the farm (OR: 0.6) were the major biosecurity risk factors in commercial poultry farms in Bangladesh.…”
Section: Discussionsupporting
confidence: 89%
“…Poor biosecurity practice is a significant risk factor for the higher prevalence of AIV [ 42 ]. Waziri et al [ 43 ] demonstrated that chickens reared in poor biosecurity practices were three times more vulnerable to be spreaders of AIV compared to good biosecurity practicing farms, which is in accordance with the current findings. Osmani et al [ 16 ] conducted a case control study and reported an increased number of farm staffs (OR: 5.2), weekly visit of veterinarians (OR: 3.0), and roaming of village chickens around the farm (OR: 0.6) were the major biosecurity risk factors in commercial poultry farms in Bangladesh.…”
Section: Discussionsupporting
confidence: 89%
“…In some African countries, illegal poaching of wild birds, which are kept in rural communities and then sold at markets, is not uncommon and may represent a possible bridge between wild and domestic birds 59 . The role of wild birds in the African continent is also supported by the virological and serological evidences of circulation of the H5 subtype in the wild population 51,60 , in particular during the most recent epidemic wave when HPAI H5N8 was widely detected in wild bird species in several countries such as Egypt 18 , Cameroon 12 , Uganda 13 and South Africa 15,17 . Moreover, in all epidemic waves the first outbreaks in Africa were reported between November and January ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 91%
“…Wild birds present a significant risk to poultry biosecurity because they can transmit disease causing agents including AIVs into poultry farms (Waziri et al, 2017). Here, apparently healthy wild birds at this wildlife and domestic birds interface were exposed to AIVs.…”
Section: Discussionmentioning
confidence: 99%